2016
DOI: 10.5194/bg-13-4111-2016
|View full text |Cite
|
Sign up to set email alerts
|

Role of zooplankton dynamics for Southern Ocean phytoplankton biomass and global biogeochemical cycles

Abstract: Abstract. Global ocean biogeochemistry models currently employed in climate change projections use highly simplified representations of pelagic food webs. These food webs do not necessarily include critical pathways by which ecosystems interact with ocean biogeochemistry and climate. Here we present a global biogeochemical model which incorporates ecosystem dynamics based on the representation of ten plankton functional types (PFTs): six types of phytoplankton, three types of zooplankton, and heterotrophic pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
167
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(173 citation statements)
references
References 134 publications
4
167
0
2
Order By: Relevance
“…Our present understanding of phytoplankton diversity and productivity in the WG, and Southern Ocean in general, is based upon bottom‐up rather than top‐down processes, in spite of the importance of grazing in the polar carbon cycle (le Quéré et al, ; Smetacek et al, ). Field experiments indicate that viral lysis of phytoplankton (both picoplankton and nanoplankton) can be relatively minor in the WG, while grazing by microzooplankton exerts significant control of phytoplankton growth (Agustí & Duarte, ; Evans & Brussaard, ; Froneman & Perissinotto, ; Henjes et al, ; Jacobsen et al, ).…”
Section: Biology I: Phytoplankton Of the Wgmentioning
confidence: 99%
“…Our present understanding of phytoplankton diversity and productivity in the WG, and Southern Ocean in general, is based upon bottom‐up rather than top‐down processes, in spite of the importance of grazing in the polar carbon cycle (le Quéré et al, ; Smetacek et al, ). Field experiments indicate that viral lysis of phytoplankton (both picoplankton and nanoplankton) can be relatively minor in the WG, while grazing by microzooplankton exerts significant control of phytoplankton growth (Agustí & Duarte, ; Evans & Brussaard, ; Froneman & Perissinotto, ; Henjes et al, ; Jacobsen et al, ).…”
Section: Biology I: Phytoplankton Of the Wgmentioning
confidence: 99%
“…1c). Elevated remineralisation driven alteration to the DIC profile at intermediate depths is associated with high POC sinking speeds and model underestimation of upper ocean bacterial biomass (0 -200 m; [35]). …”
Section: Results (A) Ocean Acidification Experimentsmentioning
confidence: 99%
“…PlankTOM10 is a global ocean biogeochemistry model which describes lower-trophic level ecosystem dynamics explicitly based on PFTs [35,54,55]. It includes ten PFTs: picophytoplankton, N2-fixers, coccolithophores, mixed phytoplankton, diatoms, colonial Phaeocystis, bacteria, protozooplankton, mesozooplankton and macrozooplankton.…”
Section: Model Description (A) Ocean Biogeochemistry Modelmentioning
confidence: 99%
“…Nor is Le Quéré convinced that the new network of floats will provide enough detail. In a paper published in July 4 , she found that models of carbon uptake by the Southern Ocean depend strongly on assumptions about the structure of the food web there. She says that climate scientists need to improve their understanding of the type and timing of phytoplankton and zooplankton blooms if they are going to get their climate projections right.…”
Section: Tracking Carbonmentioning
confidence: 99%